2020
DOI: 10.26508/lsa.202000813
|View full text |Cite
|
Sign up to set email alerts
|

A time-resolved interaction analysis of Bem1 reconstructs the flow of Cdc42 during polar growth

Abstract: Cdc42 organizes cellular polarity and directs the formation of cellular structures in many organisms. By locating Cdc24, the source of active Cdc42, to the growing front of the yeast cell, the scaffold protein Bem1, is instrumental in shaping the cellular gradient of Cdc42. This gradient instructs bud formation, bud growth, or cytokinesis through the actions of a diverse set of effector proteins. To address how Bem1 participates in these transformations, we systematically tracked its protein interactions durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 90 publications
(168 reference statements)
0
14
0
Order By: Relevance
“…Yeast Bud27 can interact with PFD2 and PFD6 (Ito et al, 2001; Deplazes et al, 2009; Wang et al, 2012). To investigate the potential interaction between AtURI and PFD members in Arabidopsis , we performed the split‐ubiquitin system assay (Johnsson and Varshavsky, 1994; Grinhagens et al, 2020) by fusing AtURI to the C‐terminal part of ubiquitin (Cub) and PFDs to the N‐terminal part of ubiquitin (Nub). The results showed that AtURI could interact with both PFD2 and PFD6, but not with PFD1, PFD3, PFD4, or PFD5 (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast Bud27 can interact with PFD2 and PFD6 (Ito et al, 2001; Deplazes et al, 2009; Wang et al, 2012). To investigate the potential interaction between AtURI and PFD members in Arabidopsis , we performed the split‐ubiquitin system assay (Johnsson and Varshavsky, 1994; Grinhagens et al, 2020) by fusing AtURI to the C‐terminal part of ubiquitin (Cub) and PFDs to the N‐terminal part of ubiquitin (Nub). The results showed that AtURI could interact with both PFD2 and PFD6, but not with PFD1, PFD3, PFD4, or PFD5 (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Yeast cells producing two interacting proteins fused to the Nub and Cub fragments will grow on medium containing 5‐FOA. Yeast transformation and analysis were based on previous studies (Johnsson and Varshavsky, 1994; Grinhagens et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This activity might be less important during bud site assembly, in which formation of the polarity patch is more rigidly defined by landmark proteins ( Lai et al, 2018 ; Chiou et al, 2017 ). The when and where of polarisome nucleation might depend on physical links between PNCs and Cdc42 GTP and/or Bem1 ( Evangelista et al, 1997 ; Grinhagens et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fir1 is predicted to present multiple linear interaction motifs within a predominately unfolded structure (Fig. 1A) (Brace et al, 2019) (Grinhagens et al, 2020; Jumper et al, 2021). Fir1 binds to Smt3 through its SUMO-interacting motif (SIM) and was recently shown to localize to the bud neck during cell abscission (Hannich et al, 2005; Uzunova et al, 2007; Brace et al, 2019; Grinhagens et al, 2020).…”
Section: Resultsmentioning
confidence: 99%